Judge's Consideration in The Case of Forgetfulness of The Cause of Death According to Islamic Criminal Law:: Study of Decision Number 238/Pid.B/2023/PN Bir - Muhtadibillah. RA, T.M. Safiir; Yahya, Faisal; Abdullah, Muslim (Teunuleh Publisher, 2025)
Criminal acts due to negligence (culpa) resulting in death are an important issue in the Indonesian criminal law system and Islamic criminal law. This research is motivated by the decision of the Bireuen District Court Number 238/Pid.B/2023/PN Bir, where the defendant was found guilty of his negligence in installing high-voltage electric wires which caused the death of another person. The formulation of the problem in this study includes how the judge considered in making a decision and how the analysis of Islamic criminal law on cases of negligence causing death to another person with the qatlul khatha' theory. This study uses a normative juridical method by analyzing the results of the decision Number 238/Pid.B/2023/PN Bir. The results of the study show that the panel of judges has determined the elements of Article 359 of the Criminal Code, but did not consider the level of negligence as conscious negligence. According to the perspective of Islamic criminal law, the defendant's actions have fulfilled the elements of qatlul khatha', therefore, it is appropriate to be charged with paying diyat and kaffarat.